A Quixotic Venture: Spanish-Philippine Poetry at the Turn of the 19th Century, or Resistance against Oblivion - Sánchez Gumiel, Mario (Humanis, 2021)
This essay explores, by means of three Philippine poems written in Spanish during the first half of the twentieth century, the claim of a Philippine cultural identity sustained in the Spanish heritage. After a short overview of the Spanish colonization in the Philippines and the presence of the Spanish language in the archipelago, I will use Paul Friedrich’s theoretical approach on poetry as a source for the study of a culture. Then I will proceed to the examination of three poems written by Philippine writers: Fernando María Guerreros’ “A Hispania” (1913), Claro Mayo Recto’s “Las dalagas Filipinas” (1911), and Jesús Balmori’s “Blasón” (undated) by means of the close reading approach. In the exploration of this claim of a Philippine cultural identity rooted in the Spanish heritage, I additionally consider the role of the United States, and take into account some initiatives that have tried to continue the study of this literature throughout the twentieth and twenty-first century. I conclude that poetry is a valuable way to analyse culture, and, for the specific case of Spanish and the Philippines, I suggest that Spanish-Philippine poetry helps know the heritage of Spanish in the archipelago